Hosts and guests : the anthropology of tourism - Smith, Valene L. (University of Pennsylvania Press, 1989)
Tourism--one of the world's largest industries--has long been appreciated for its economic benefits, but in this volume tourism receives a unique systematic scrutiny as a medium for cultural exchange. Modern developments in technology and industry, together with masterful advertising, have created temporarily leisured people with the desire and the means to travel. They often in turn effect profound cultural change in the places they visit, and the contributors to this work all attend to the impact these "guests" have on their "hosts."In contrast to the dramatic economic transformations, the social repercussions of tourism are subtle and often recognized only by the indigenous peoples themselves and by the anthropologists who have studied them before and after the introduction of tourism. The case studies in Hosts and Guests examine the five types of tourism--historical, cultural, ethnic, environmental, and recreational--and their impact on diverse societies over a broad geographical range.